Histological Study on the Effect of Ampiroxicam Drug on liver of Females Mice - Kh. Hussain, Zainab; Kh. Hussain, Zainab (Iraqi Journal of Science, 2023)
Thirty females’ albino mice with average body weight of 25-30gm and 10-14 weeks old were used to investigate the toxicity of the oral administration of ampiroxicam on liver. The animals were given (single dose) of drug and were divided into three groups (10mice / group), control group were given distilled water, the two remaining groups ( treated group2 were administered by 20 mg/kg of ampiroxicam for one month and treated group3 were administrated by20 mg/kg of ampiroxicam for tow month). The results showed that the changes in of tissue of liver in treated animals include: degeneration of hepatocyte and hepatic sinusoidal dilation, also lymphocyte infiltration, necrosis, dead cell, detachment of basement membranes and hypertrophy while there are no significant microscopic changes in control group1 (untreated animals). The increase in duration of the oral administration of ampiroxicam has increasing significant effect on liver of mice.